Prototype Rickettsia Ricketsii Vaccine Candidate - Ibrahim Mohamed Saeed Shnawa (Vaccines and Vaccine Interference, 2023)
Candidate vaccines for Rickettsia rickettsia are still of prototype and experimental nature. Whole cell live attenuated, inactivated and dead were the first generation vaccine versions. These vaccines had been proved in mammalian small laboratory animal models as partial immune protectant on experimental challenge with live agent infectious doses. Viral vector cloned with recombinant DNA sequence encoding membrane proteins OMPA and OMPB were found as pure safe, antigenic and immunogenic and immune protectant in guinea pigs and mice. While recombinant DNA sequence encoding OMPB 4 protein were found as pure safe, antigenic and immunogenic but in effective in immune protection in a canine model. Promising approved human vaccine for this agent seemed to be far from being reached since many facets of immune protection and immunopathology need to be explored. Five years or more wait for establishing safe immune protective vaccine for human welfare.